2020
DOI: 10.2147/idr.s249475
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mechanisms of Heteroresistance and Resistance to Imipenem in <em>Pseudomonas aeruginosa</em></p>

Abstract: Background: Heteroresistance is a phenomenon that occurs in all bacteria and can cause treatment failure. Yet, the exact mechanisms responsible for heteroresistance still remain unknown. The following study investigated the mechanisms of imipenem-heteroresistance and -resistance in Pseudomonas aeruginosa clinical isolates from Wenzhou, China. Methods: Imipenem resistance was detected by the agar dilution method; heteroresistance was determined by population analysis profiles. Biofilm formation assay and modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…However, due to the amino acid variability within the susceptible group, we could not determine any significant mutation that might correlate with their resistance to Im; thus, other molecular mechanisms may take place. Our results agree with previous reports that indicated that truncated OprD proteins are responsible for the resistance to Im ( 29 ).…”
Section: Resultssupporting
confidence: 93%
“…However, due to the amino acid variability within the susceptible group, we could not determine any significant mutation that might correlate with their resistance to Im; thus, other molecular mechanisms may take place. Our results agree with previous reports that indicated that truncated OprD proteins are responsible for the resistance to Im ( 29 ).…”
Section: Resultssupporting
confidence: 93%
“…Since then, a variety of novel MBLs have been described in Gram-negative bacteria, including AIM (Australian Imipenemase), DIM (Dutch Imipenemase), GIM (German Imipenemase), KHM (Kyorin University Hospital), NDM (New Delhi MBL), SIM (Seul Imipenemase), SPM (Sao Paulo MBL), and TMB (Tripoli MBL) [219,220]. In laboratory conditions, carbapenemases may be differentiated through the inhibition of various molecules (e.g., ethylenediaminetetraacetic acid for MBLs, boronic acid for serine-type enzymes), but it is more difficult to carry out due to the low outer membrane permeability of P. aeruginosa, which may significantly alter the resistance phenotype [221,222].…”
Section: Main Mechanisms Of β-Lactam-resistance In P Aeruginosamentioning
confidence: 99%
“…For example, heteroresistance to tigecycline in Salmonella enterica was associated with an increased level of the RamA transcriptional factor, resulting in the overexpression of the AcrAB-TolC and OqxAB efflux pumps [ 35 ]. Other studies have indicated that the downregulation of the OprD porin and overexpression of the efflux systems contributed to carbapenem and imipenem heteroresistance in Pseudomonas aeruginosa [ 38 , 41 ].…”
Section: Heteroresistance: Definition Detection Methods and Underlying Mechanismsmentioning
confidence: 99%